Live virus vaccines based on a yellow fever vaccine backbone: Standardized template with key considerations for a risk/benefit assessment. Issue 1 (1st January 2015) - Monath, Thomas P.; Seligman, Stephen J.; Robertson, James S.; Guy, Bruno; Hayes, Edward B.; Condit, Richard C.; Excler, Jean Louis; Mac, Lisa Marie; Carbery, Baevin; Chen, Robert T.; The Brighton Collaboration Viral Vector Vaccines Safety Working Group (V3SWG), 4
Highlights The Brighton Collaboration Viral Vector Vaccines Safety Working Group (V3SWG) evaluates vaccine safety. Many recombinant viral vectored vaccines are in advanced clinical trials. A template is presented for evaluating live recombinant flavivirus vaccines in which genes for envelope proteins have replaced the corresponding genes in yellow fever virus vaccine. The template can be used as a model for other live recombinant viral vaccines.